Development, Branding, and Marketing Strategy of Mulberry Leaf Tea Products in Food Technology - Qizi, Vakilova Sitora Tillaboy (American Journal of Biology and Natural Sciences, 2025)
This paper explores the development, branding, and marketing strategy of mulberry leaf tea as an innovative food technology product. Mulberry leaves are rich in bioactive compounds, antioxidants, and natural flavors that make them suitable for functional tea production. The study reviews technological processes for producing high-quality mulberry leaf tea and outlines effective branding and marketing approaches for increasing its global competitiveness. The integration of food technology and strategic marketing offers opportunities to enhance the commercial potential of mulberry-based tea products. This conceptual study provides an overview of the technological parameters, product differentiation, and market positioning strategies necessary for successful commercialization of mulberry leaf tea.